P16INK4a as a proliferation marker unrelated to HPV expression in odontogenic cysts and tumors. (20th November 2019) - Hakeem, Abdulaziz; Fitzpatrick, Sarah G.; Gonsalves, Catherine A.; Isom, James; Islam, Mohammed N.; Bhattacharyya, Indraneel; Cohen, Donald M.; Drew, Peter A.
Abstract: Introduction: p16INK4a is a tumor suppressor protein that retards cell cycle progression from G1 to S phase. Prior studies have evaluated p16INK4a expression in odontogenic keratocyst and ameloblastoma, but data regarding other odontogenic cysts and tumors have been sparse. Methods: With IRB approval, cases from the following entities were identified from archives of the UF Oral Pathology Biopsy Service (2005‐2015): benign incidental odontogenic rest, dentigerous cyst, lateral periodontal cyst, calcifying odontogenic cyst, glandular odontogenic cyst, odontogenic keratocyst, orthokeratinized odontogenic cyst, adenomatoid odontogenic tumor, calcifying epithelial odontogenic tumor, and ameloblastoma. All cases were submitted for p16INK4a immunohistochemical testing. Results: Results were scored as follows: nuclear and cytoplasmic staining of <5% cells (score 0), 5%‐25% (score 1), 25%‐50% (score 2), >50% (score 3). No significant difference in p16INK4a staining was noted between odontogenic cysts and the listed odontogenic tumors ( chi‐square, P = .540). When comparing lesions with higher recurrence rates (over 25% as reported in the literature) versus lesions with low recurrence rates (under 25%), higher recurrence correlated to significantly higher p16INK4a positivity ( chi‐square, P = .001). Follow‐up testing was performed on 18 cases with "2" or "3" p16INK4a expression scores for high‐risk HPV strains through HPV in situ hybridization (ISH) messenger RNA testing with no cases exhibiting a positive result. Conclusion: This study exhibits an association between increased p16INK4a positivity and odontogenic lesions with higher recurrence rates and highlights the role of p16INK4a as a progression marker unrelated to HPV expression in this group of pathologic entities.